Psychometric properties and validation of the critical reasoning assessment - Fabio, Rosa Angela; Plebe, Alessio; Ascone, Chiara; Suriano, Rossella (Personality and individual differences, 2025)
AbstractCritical reasoning is essential for both academic and professional success, as it enhances analytical abilities, decision-making skills, and adaptability in a constantly evolving environment. This study aims to adapt and validate the Critical Reasoning Assessment (CRA) for the Italian population. A pilot test with 79 participants addressed initial issues and confirmed the CRA's ability to differentiate between high and low performers. The first study, involving 123 participants, validated the CRA's unidimensional structure and consistency in measuring critical reasoning. A subsequent study with 480 participants further supported this structure, showing strong fit indices. The adaptation process included translation and back-translation by bilingual experts to ensure linguistic accuracy. The CRA demonstrated excellent reliability (Cronbach's alpha = 0.93) and showed strong convergent validity through positive correlations with the Critical Reasoning Disposition Inventory and academic performance, as well as divergent validity through negative correlations with dysfunctional beliefs. These findings confirm the CRA's effectiveness as a reliable tool for evaluating critical reasoning performance.